Emerging Applications for Quantitative Susceptibility Mapping in the Detection of Traumatic Brain Injury Pathology. (15th July 2021) - Gozt, Aleksandra; Hellewell, Sarah; Ward, Phillip G.D.; Bynevelt, Michael; Fitzgerald, Melinda
Highlights: Traumatic brain injury (TBI) elicits a complex pathophysiological response. Iron has been increasingly implicated in the pathology of TBI. Quantitative Susceptibility Mapping (QSM) is a novel neuroimaging technique. QSM may be used to investigate iron-related changes following TBI. Existing literature in which QSM has been utilised within a TBI context is reviewed. Abstract: Traumatic brain injury (TBI) is a common but heterogeneous injury underpinned by numerous complex and interrelated pathophysiological mechanisms. An essential trace element, iron is abundant within the brain and involved in many fundamental neurobiological processes, including oxygen transportation, oxidative phosphorylation, myelin production and maintenance, as well as neurotransmitter synthesis and metabolism. Excessive levels of iron are neurotoxic and thus iron homeostasis is tightly regulated in the brain, however, many details about the mechanisms by which this is achieved are yet to be elucidated. A key mediator of oxidative stress, mitochondrial dysfunction and neuroinflammatory response, iron dysregulation is an important contributor to secondary injury in TBI. Advances in neuroimaging that leverage magnetic susceptibility properties have enabled increasingly comprehensive investigations into the distribution and behaviour of iron in the brain amongst healthy individuals as well as disease states such as TBI. Quantitative Susceptibility Mapping (QSM) is an advanced neuroimaging technique that promises quantitative estimation of local magnetic susceptibility at the voxel level. In this review, we provide an overview of brain iron and its homeostasis, describe recent advances enabling applications of QSM within the context of TBI and summarise the current state of the literature. Although limited, the emergent research suggests that QSM is a promising neuroimaging technique that can be used to investigate a host of pathophysiological changes that are associated with TBI.